Guiding system for visually impaired running on a track - Kemeth, F.; Hafenecker, S.; Jakab, S.; Varga, M.; Tamás Csielka; Couronné, S. (Sports Science Research and Technology Support: Second International Congress, icSPORTS 2014, Rome, Italy, October 24-26, 2014, Revised Selected Papers, 2015)
Sighted people can enjoy many social activities that the visually impaired are denied. Our project has the major goal to develop a guidance system: A real-time locating system (RTLS) based on radio signals guides runners with the highest level of safety by estimating the angle of arrival (AoA) and round-trip time (RTT). First results show the position accuracy of the proposed locating system with real-world data with a deviation of less than one metre. Thus we provide an enormous freedom for the visually impaired runners compared to the other solutions: Blind and sighted runners will have the opportunity to do sport together without another person`s assistance.